Terpenoid-Mediated Targeting of STAT3 Signaling in Cancer: An Overview of Preclinical Studies - Fahad Khan; Pratibha Pandey; Meenakshi Verma; Tarun Kumar Upadhyay (Biomolecules, 2024)
Cancer has become one of the most multifaceted and widespread illnesses affecting human health, causing substantial mortality at an alarming rate. After cardiovascular problems, the condition has a high occurrence rate and ranks second in terms of mortality. The development of new drugs has been facilitated by increased research and a deeper understanding of the mechanisms behind the emergence and advancement of the disease. Numerous preclinical and clinical studies have repeatedly demonstrated the protective effects of natural terpenoids against a range of malignancies. Numerous potential bioactive terpenoids have been investigated in natural sources for their chemopreventive and chemoprotective properties. In practically all body cells, the signaling molecule referred to as signal transducer and activator of transcription 3 (STAT3) is widely expressed. Numerous studies have demonstrated that STAT3 regulates its downstream target genes, including Bcl-2, Bcl-xL, cyclin D1, c-Myc, and survivin, to promote the growth of cells, differentiation, cell cycle progression, angiogenesis, and immune suppression in addition to chemotherapy resistance. Researchers viewed STAT3 as a primary target for cancer therapy because of its crucial involvement in cancer formation. This therapy primarily focuses on directly and indirectly preventing the expression of STAT3 in tumor cells. By explicitly targeting STAT3 in both in vitro and in vivo settings, it has been possible to explain the protective effect of terpenoids against malignant cells. In this study, we provide a complete overview of STAT3 signal transduction processes, the involvement of STAT3 in carcinogenesis, and mechanisms related to STAT3 persistent activation. The article also thoroughly summarizes the inhibition of STAT3 signaling by certain terpenoid phytochemicals, which have demonstrated strong efficacy in several preclinical cancer models.